Cypermethrin Promotes Lung Cancer Metastasis via Modulation of Macrophage Polarization by Targeting MicroRNA-155/Bcl6. (19th February 2018) - Huang, Fang; Chen, Zhifeng; Chen, Hanwen; Lu, Wei; Xie, Shujun; Meng, Qing H; Wu, Yihua; Xia, Dajing
Abstract: Cypermethrin (CYM), a type II pyrethroid, is widely used as an insecticide for agriculture and household. Cumulative evidence indicates that acute and chronic exposure to CYM might cause a number of health problems, such as cancer and neuronal system diseases. However, the molecular mechanism underlying this pathology is not known. The main objective of this study was to define the effects of CYM on macrophages and the implication of such effects in cancer metastasis and the potential mechanism involved. The effects of CYM on the macrophages were evaluated by detecting the expression of M1 and M2 macrophage polarization markers through ELISA, quantitative RT-PCR, and Western blot assay. Transwell and wound healing assays were used to test the migration of lung cancer cells after exposure to CYM in vitro and a metastasis animal model in vivo . Treatment with CYM significantly suppressed lipopolysaccharide (LPS)-induced M1 macrophage polarization and promoted a shift toward M2 macrophage status. Mechanistically, CYM downregulated miR-155 significantly, leading to enhanced expression of its target gene Bcl6, thereby reducing the expression of mitogen-activated protein kinase 4 (MKK4), an upstream kinase of c-Jun N-terminal kinases (JNK), and inhibiting JNK activation. Impaired JNK activation thus promoted a shift in macrophage polarization from the M1 to the M2 phenotype. Finally, CYM-treated macrophages promoted metastasis of Lewis lung cancer cells in both in vitro and in vivo models. Taken together, our findings show that CYM is able to inhibit the M1 polarization and promote the macrophages to the M2 phenotype, which plays an important role in tumor metastasis.